Millennials’ Intention in Stock Investment: Extended Theory of Planned Behavior - Mahardhika, Arya Samudra; Zakiyah, Tuti (Universitas Muhammadiyah Surakarta, 2020)
The main objective of this research was to empirically examine the interests of millennial investors in investing in stocks using the theory of planned behavior approach consisting of Attitude toward Behavior, Subjective Norms, and Perceived Behavior Control as predictors of Intention, and Actual Behavior as a consequence of Intention. In addition, this research added risk tolerance variable as a development. This research is based on the low investment interest of the Indonesian people when compared to the total population of Indonesia. Respondents in this study are investors who are in accordance with predetermined criteria, who have already invested in stock and are aged between 20-35 years in Kebumen Regency. Data collection in this study was carried out by distributing questionnaires to the respondents. The hypothesis in this research was tested using Structural Equation Modeling (SEM) through WarpPLS software version 6.0. The results of hypothesis testing in this research empirically prove that Attitude toward Behavior, Subjective Norms, and Perceived Behavior Control are predictors of Intention. In addition, this research also proves that Intention has a positive effect on millennial investors’ actual behavior in investing in stocks.